RE-THINKING OF WOMEN PoRSTITUTION : PROBLEM OF GENDER PERSPECTIVE - Fahmi, Reza; Jamaldi, Jamaldi (Universitas Islam Negeri Imam Bonjol Padang, 2019)
This research departed from the fact that the Tsunami natural disaster had just passed in Palu, Central Sulawesi. Research objectives: (1) Describe the views of the community about women in the problem of prostitution. (2) Describe gender bias about the stigmatization of women towards the emergence of prostitution that carries a tsunami. (3) Describe the influence of stigmatization of women on their psychological pressure as the cause of the Tsunami. This study uses a quantitative approach. The populations in this study were 287 people using social media (Facebook). The sample in this study was 167 people. The data collected by a psychological scale and documentation study. Analyzed data was used simple regression. The results of this study found the influence of stigmatization of women on the emergence of psychological pressure they received over the Tsunami month ago.